Heterogeneity of nutritional habits of Lithuanian ethnolinguistic groups: population-based study - Jakaitienė, Audronė; Austys, Donatas; Burokienė, Neringa; Kasiulevičius, Vytautas; Stukas, Rimantas; Kučinskas, Vaidutis (Acta medica Lituanica, 2016)
Background. Lithuania is a Northern European country consisting of two main ethnolinguistic groups: Samogitians and Highlanders. The objective of the paper is to investigate differences in nutritional habits of 18–65-year-old Lithuanians living in different ethnolinguistic regions. Materials and methods. A representative, population-based, random sample of the 18–65-year-old ethnic Lithuanian population was interviewed from 17 December 2008 to 20 May 2013. Lithuanians living in their ethnolinguistic region for at least three generations were included (n = 1,133). We analysed responses to 12 questions about nutritional habits of respondents. For the univariate analysis, we applied the chi-squared test. For the clusterisation of the survey questions, we employed a multiple correspondence analysis (MCA). Results. Comparing Samogitians’ and Highlanders’ responses according to their gender, education, and place of residence, we observed more often significant differences (p